Development of Plant Bioplastic Learning Media Equipped with QR Codes to Improve Students' Understanding of Biodiversity Material - Rahmadani, Riska Arifa; Rudyatmi, Ely (Universitas Negeri Semarang, 2025)
In the Merdeka Curriculum, students are required to explore knowledge and skills from their own experiences. So far, teachers have been using picture, video, and PowerPoint media. Students' understanding of biodiversity is lacking because they do not have direct experience in classifying plants. Therefore, it is necessary to develop plant bioplastic media equipped with QR codes as an effort to improve students' understanding. The purpose of this research is to analyze the validity, practicality, and effectiveness of plant bioplastic learning media equipped with QR codes. This research uses the Research and Development (R&D) method with the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The research was conducted at SMA N 1 Bawang in the Academic Year 2023/2024. The research design used during the implementation phase was the Non-Equivalent Pretest Posttest Control Group Design. The validity of the media and materials was determined using validation questionnaires. The practicality of the media was determined based on teacher and student response questionnaires. The effectiveness of the media was determined based on student test results and student worksheets. Validity and practicality were analyzed descriptively, while effectiveness was analyzed quantitatively. The results of the validator assessment stated that the plant bioplastic media was highly valid. Teachers found the media to be very practical, and all students rated the media as practical or very practical. The Mann-Whitney test revealed that the learning outcomes of the experimental class were significantly higher than those of the control class. The number of students with medium and high N-gain in the experimental class was greater than that in the control class, namely 59% > 39%. Plant bioplastic media equipped with QR codes is valid, practical, and effective in improving students' understanding of biodiversity.